Model for developing corporate communication strategy - Benita Steyn (Communicare)
The body of knowledge in the field of corporate communication indicates a strategic role for the corporate communication manager. However, there are but a few references to corporate communication 'strategy' in a strategic organisationa( context. Few practitioners seem to understand the meaning of strategy, although it is a known, uncomplicated concept to those familiar with management theory. The key problem seems to lie in the application of strategy for corporate communication (public relations) issues. It is therefore the aim of this article to explain the meaning of strategy in a corporate communication context. Based on the strategic management Literature, corporate communication strategy is conceptualised as a functional strategy, providing focus and direction to the corporate communication function. It is differentiated from implementation strategy as it is known in the communication plan - the latter being the approach to communication activities. Corporate communication strategy is proposed as providing the missing link between the corporate strategy and the corporate communication function.